Recommendation of Phosphate and Potassium Fertilizers for Maize at Five Locations in Lampung - Barus, Junita; Murni, Andarias Makka (JOURNAL OF TROPICAL SOILS, 2010)
Recommendation of Phosphate and Potassium Ferlilizers for Maize at Five Location in Lampung (J Barus and AM Murni):. Fertilizer recommendation in specific location will be related to fertilizers efficiency.  The study was conducted at five locations which were planted with corn minimal once a year, namely: (1) Sidowaras village,  Bumi Ratu Nuban Subdistrict, Lampung Tengah Regency; (2) Binjai Ngagung,  Bekri Subdistrict, Lampung Selatan Regency; (3) Watu Agung,  Kalirejo Subdistrict, Lampung Tengah Regency, (4) Balai Rejo, Kalirejo Subdistrict, Lampung Tengah Regency, and (5) Trimulyo, Tegineneng Subdistrict, Lampung Selatan Regency.  The soil samples were analyzed in the Research and Development Centre for Soil and Agroclimate Laboratory in Bogor.  The value of  P and K in soil were compared to the results of  correlation study using several extraction of P and K in Lampung.  Results of the study showed that the status of P was high for three location, medium for one location and low for one location.  K status was low for five locations. Phosphorus fertilizer  recommendation on the three locations with high level of P (Sidowaras, Binjai Ngagung, and Balai Rejo) was 75 kg ha-1 SP-36, on the middle P levels (Trimulyo) was 150 kg and on the low level of P (Watu Agung) was 300 kg. On the other hand, the recommendation for K fertilizer for all locations were 150 kg ha-1 KCl.